Rancang Bangun E-learning Berbasis Web Sebagai Media Interactive on line Learning - Daru, April Firman (Universitas Semarang, 2014)
Class teaching and learning process has shortcomings, namely limited Class schedule. If the teacher is not in place, the course can not be done. Submission of materials consequently delayed. Utilization of the web as a tool in the lecture can resolve the issue. When the teacher was not there, the lecture could still walk, student attendance can be monitored, the discussion can be done and the task can check on line. Based on these problems will be developed interactive learning web-based application that can be a means of lectures. Model development system used in use is the System Product Development Life Cycle.